Luizenses: patrimônio de São Luiz do Paraitinga - Antunes, Bruna Fabio [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The fight for overcoming and personal reconstruction from the individual keeps fascinating great part of the humanity. Maybe because we search for similarities in our misfortunes, maybe because we wish to have a model to follow on situations that, in the beginning, we haven't known how to face it. The fact is that many times, human being surprises himself with his own overcoming power. In light of this, this work aim to present to the public the overcoming and the transformation process of the habitants of São Luiz do Paraitinga, city from the state of São Paulo that was covered by floods in January 2010. The intention is not to show the physic reconstruction of the city, but the personal reconstruction of the habitants that had their lives modified, literally, overnight. The documentary format was chosen to approach the public with the characters, their histories and their emotions, keeping the timeless of situations that will still be remembered for a long time

A luta pela superação e reconstrução pessoal do indivíduo continua a fascinar grande parte da humanidade. Talvez porque buscamos semelhanças em nossos infortúnios, talvez porque desejamos nos espelhar em situações que, a princípio, não soubemos enfrentar. O fato é que, muitas vezes, o ser humano se surpreende no seu próprio poder de superação. Tendo isso em vista, este trabalho visa apresentar ao público o processo de superação e mesmo de transformação dos moradores de São Luiz do Paraitinga, cidade do interior do estado São Paulo que foi assolada pelas enchentes em janeiro de 2010. A intenção é mostrar não a reconstrução física da cidade, mas a reconstrução pessoal dos moradores, que tiveram suas vidas modificadas, literalmente, da noite para o dia. O formato documentário foi escolhido para aproximar o público dos personagens, de suas histórias e de suas emoções, mantendo a atemporalidade de casos que ainda serão lembrados por muito tempo
Keywords: Jornalismo cidadão; Inundações; Cidades e vilas; Reconstrução; Documentario (Cinema); Fotojornalismo; Citizen journalism; São Luiz do Paraitinga (SP)